2014
DOI: 10.21608/jssae.2014.49842
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation Cut-Off as Efficient Scheme for Maximizing Cantaloupe Productivity and Quality Under Different Iron Application Techniques

Abstract: Two field experiments were conducted to quantify the response of cantaloupe crop (Cucumis melo, Hybrid French F1) to variable irrigation regimes and Fe-fertilizer application techniques on some irrigation parameters, fruit yield, yield components, water consumption and some crop -water relations. Four cut-off irrigation regimes were assessed e.g. stop irrigation as the water front reached 100 (control), 90, 80 and 70% of the entire furrow length(FL). Four iron application techniques e.g. in soil (Fe1), foliar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Kassab et al (2012) reported that using irrigation cut-off at 90 % of strip length in North Nile Delta gave the same yield of berseem as obtained from irrigation cut-off at 95% of strip length, but it saved 7.9% of irrigation water and gave the highest water use efficiency (24.80 kg m 3 ) and water productivity (16.58 kg m 3 ). Darwesh and Farrag (2014) advised to irrigate cantaloupe crop using 90% irrigation cut-off under North Nile Delta conditions. Kassab and Ibrahim (2007) stated that irrigation cut-off with wheat was effective technique for water saving; and the irrigation cut-off at 90% of strip length gave the highest values of water use efficiency (1.73kg.m -3 ) and water productivity (1.61kg.m -3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kassab et al (2012) reported that using irrigation cut-off at 90 % of strip length in North Nile Delta gave the same yield of berseem as obtained from irrigation cut-off at 95% of strip length, but it saved 7.9% of irrigation water and gave the highest water use efficiency (24.80 kg m 3 ) and water productivity (16.58 kg m 3 ). Darwesh and Farrag (2014) advised to irrigate cantaloupe crop using 90% irrigation cut-off under North Nile Delta conditions. Kassab and Ibrahim (2007) stated that irrigation cut-off with wheat was effective technique for water saving; and the irrigation cut-off at 90% of strip length gave the highest values of water use efficiency (1.73kg.m -3 ) and water productivity (1.61kg.m -3 ).…”
Section: Introductionmentioning
confidence: 99%